The Eleian Mantic Gene. (2014) - Bourke, Graeme
Abstract: The Eleian manteis who practised at the altar of Zeus in Olympia appear to have belonged to two separate gene, the Iamids and the Klytiads. This paper first considers the identity and number of the Eleian mantic gene and then questions the long-held assumption that the Iamid genos was the first to become established at Olympia. It is argued that the foundation myths that appear in Pindar and Pausanias are probably the result of the embellishment of pre-existing tradition in the Classical and Hellenistic periods. While neither archaeology nor further textual evidence entitles us to assume that mantic activity at Olympia predated the late Archaic period, an early Classical inscription, certain of the sculptures on the temple of Zeus and a later series of inscriptions from Olympia do make it possible to infer that two mantic houses, of which the Iamids were one and the Klytiads likely the other, were practising at Olympia from that time or earlier. Some reflection upon the limitations of myth as historical evidence is offered before the conclusion is reached that we cannot be certain that the Iamids constituted the senior house.